Impact of shelter-in-place order for COVID-19 on trauma activations: Santa Clara County, California, March 2020. Issue 1 (7th May 2020) - Forrester, Joseph D; Liou, Raymond; Knowlton, Lisa M; Jou, Ronald M; Spain, David A
Abstract : Introduction: The shelter-in-place order for Santa Clara County, California on 16 March was the first of its kind in the USA. It was unknown what impact this order would have on trauma activations. Methods: We performed a retrospective analysis of institutional trauma registries among the two American College of Surgeons Level 1 trauma centers serving Santa Clara County, California. Trauma activation volumes at the trauma centers from January to March 2020 were compared with month-matched historical cohorts from 2018 to 2019. Results: Only 81 (3%) patients were trauma activations at the trauma centers in the 15 days after the shelter-in-place order went into effect on 16 March 2020, compared with 389 activations during the same time period in 2018 and 2019 (p<0.0001). There were no other statistically significant changes to the epidemiology of trauma activations. Only one trauma activation had a positive COVID-19 test. Discussion: Overall trauma activations decreased 4.8-fold after the shelter-in-place order went into effect in Santa Clara County on 16 March 2020, with no other effect on the epidemiology of persons presenting after traumatic injury. Conclusion: Shelter-in-place orders may reduce strain on healthcare systems by diminishing hospital admissions from trauma, in addition to reducing virus transmission.